Theabrownin Induces Cell Apoptosis and Cell Cycle Arrest of Oligodendroglioma and Astrocytoma in Different Pathways - Fu, J. Y.; Jiang, C. X.; Wu, M. Y.; Mei, R. Y.; Yang, A. F.; Tao, H. P.; Chen, X. J.; Zhang, J.; Huang, L.; Zhao, X. F. (Frontiers in Pharmacology, 2021)
Theabrownin (TB), a natural compound produced by the fresh leaves of Green Tea, is a potential anti-tumor agent. However, so far whether and how TB affect glioma is unclear. In this study, we investigated the effect of TB on astrocyte and oligodendrocyte glioma cells. Surprisingly, TB significantly reduced the viabilities of HOG and U251 cells in a dose-dependent manner, which was accompanied by the up-regulation of Casp-3, Bax and PTEN. In additional, TB treatment induced cell cycle arrest at the G1 and G2/M phase in HOG and U251 cells, respectively, and down-regulating of c-myc, Cyclin D, CDK2, CDK4 and up-regulating of p21, p27 in the HOG cell, while increasing P53 and P21 levels and decreasing levels of the cell cycle regulator proteins such as CDK, Cyclin A/B in the U251 cells. Therefore, the c-myc- and P53-related mechanism were thereby proposed for cell cycle arrest in these two glioma cell lines, respectively. Overall, our findings indicated TB acted as a candidate for anti-cancer drug development in the treatment of glioma.